Application of an association of yeast and lactic acid bacteria to bioencapsulate carotenoids in Daphnia magna (Straus, 1820) - Vasina, Liliia; Чебан, Лариса (My University, 2020)
Freshwater zooplankton, which is commonly used as a starting fish feed, has a low content of essential compounds such as carotenoids. The possibility of increasing the productivity of carotenogenic yeast, Rhodotorula glutinis, for further bioencapsulation of zooplankton Daphnia magna is shown. An association of a UV irradiated yeast strain with lactic acid bacteria was cultivated for this purpose. This permitted intensifying the carotenogenesis of yeast, and the content of â-carotene increased by 1.7 times, and that of torularodine by 2.3 times compared with the native monoculture. The use of the association of microorganisms as a feed substrate in the cultivation of Daphnia magna provided both an increase in the carotenoid content in the investigated crustaceans more than 8 times, and their biomass by 2.5 times compared with the standard feed of Saccharomyces cerevisiae.
Keywords: enriched live feed; essential compounds; lactic acid bacteria; Rhodotorula glutinis; zooplankton